2004
DOI: 10.1159/000081656
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Oral Fluoride Retention 3 Minutes after Fluoride Mouthrinsing in 4- to 5-Year-Old Children: Effects of Fluoride Concentration and Rinsing Time

Abstract: This study was undertaken to explore the site-specific retention rate and the possibility of shortening fluoride (F) mouthrinsing time of kindergarten children. Fluoride retention after 10-, 20- and 30-second mouthrinsing was determined in 43 kindergarten children aged 4–5 years. Tooth surfaces were sampled by a paper point method. Fluoride concentrations in the salivary film on tooth surfaces increased from primary molars to primary incisors in the maxilla and decreased from primary molars to primary incisors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…However, according to the present study, it is likely that the effect is even better in individuals with hyposalivation. When the individuals with hyposalivation rinsed with 0.2% NaF solution for a shorter time than recommended (i.e., 20 seconds), the F concentration and duration, measured as AUC in saliva and interproximal fluid, were similar compared to 1 minute rinsing, a result in line with a previous study conducted by Adachi et al . The swab method in our study showed somewhat lower AUC values in saliva, but similar interproximally values, compared to 1 minute rinsing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, according to the present study, it is likely that the effect is even better in individuals with hyposalivation. When the individuals with hyposalivation rinsed with 0.2% NaF solution for a shorter time than recommended (i.e., 20 seconds), the F concentration and duration, measured as AUC in saliva and interproximal fluid, were similar compared to 1 minute rinsing, a result in line with a previous study conducted by Adachi et al . The swab method in our study showed somewhat lower AUC values in saliva, but similar interproximally values, compared to 1 minute rinsing.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, there is a demand for F products and procedures that require a minimum ability to cooperate or none at all. Although the directions for using the F mouthrinse are to rinse for 1 minute, a sufficient effect seems to be reached already after rinsing for 20–30 seconds . This shortened rinsing period could make it possible for many people with cognitive impairments to use the product.…”
Section: Introductionmentioning
confidence: 99%